Panel Binary Variables and Sufficiency: Generalizing Conditional Logit - Magnac, Thierry (Econometrica, 2004)
This paper extends the conditional logit approach (Rasch, Andersen, Chamberlain) used in panel data models of binary variables with correlated fixed effects and strictly exogenous regressors. In a two-period two-state model, necessary and sufficient conditions on the joint distribution function of the individual-and-period specific shocks are given such that the sum of individual binary variables across time is a sufficient statistic for the individual effect. By extending a result of Chamberlain, it is shown that root-n consistent regular estimators can be constructed in panel binary models if and only if the property of sufficiency holds. In applied work, the estimation method amounts to quasi-differencing the binary variables as if they were continuous variables and transforming a panel data model into a cross-section model. Semiparametric approaches can then be readily applied.